The Book of Negroes Data - Dragovich, Joe (2022)
A JSON formatted version of the 1783 historical document The Book of Negroes. In 1783, the new United States demanded that the British return the enslaved people that had fled to their lines during the war. The British refused and evacuated them from New York.
original-date: 2020-02-11T21:57:19Z https://mapping-freedom.dragovich.co.uk/
Keywords: _18e; _open access

The Black Press
Keywords: _open access